2016
DOI: 10.1111/1751-2980.12381
|View full text |Cite
|
Sign up to set email alerts
|

EUS‐guided FNA and FNB after on‐site cytological evaluation in gastric subepithelial tumors

Abstract: EUS-FNB decreases the number of needle passes to obtain adequate cellularity and yields a higher proportion of adequate cellularity during the first needle pass compared with EUS-FNA in gastric SETs. However, there was no significant difference in diagnostic yield with IHC stain between the two procedures after on-site cytological evaluation for adequate cellularity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 21 publications
1
39
0
Order By: Relevance
“…These needles were designed to augment the quantity and quality of the samples obtained and improve diagnostic yields by preserving the structural integrity of the tissues . Findings from some randomized controlled trials that compared reverse‐bevel FNB needles and FNA needles have shown that although the needles did not differ with respect to the subsequent diagnostic accuracies for solid masses that mainly comprised pancreatic tumors, the histological quality of the samples obtained by FNB needles was higher and the samples were frequently more satisfactory for histological diagnoses . Consequently, recent guidelines recommend FNB and FNA needles equally for routine EUS‐guided sampling; however, the same guidelines also indicate a weak recommendation for FNB needles to be used when the aim of sampling is to obtain a core tissue specimen .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These needles were designed to augment the quantity and quality of the samples obtained and improve diagnostic yields by preserving the structural integrity of the tissues . Findings from some randomized controlled trials that compared reverse‐bevel FNB needles and FNA needles have shown that although the needles did not differ with respect to the subsequent diagnostic accuracies for solid masses that mainly comprised pancreatic tumors, the histological quality of the samples obtained by FNB needles was higher and the samples were frequently more satisfactory for histological diagnoses . Consequently, recent guidelines recommend FNB and FNA needles equally for routine EUS‐guided sampling; however, the same guidelines also indicate a weak recommendation for FNB needles to be used when the aim of sampling is to obtain a core tissue specimen .…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have investigated the diagnostic yields associated with the use of FNB needles to sample SET, and only four published reports have described studies that have compared SET sampling using FNB and FNA needles (Table ). Three of these studies included small sample sizes of approximately 10–20 cases, and the findings from two of these studies showed that the diagnosis rates associated with the use of FNB needles were significantly higher than those associated with the use of FNA needles (75% vs 20%, respectively; P = 0.01; and 87% vs 53%, respectively; P = 0.01), but the other study's findings did not show a significant difference between the needle types regarding the diagnostic rate (82% vs 68%, respectively; P = 0.488) . The remaining study's findings showed that the diagnostic accuracy associated with the use of FNB needles (83%) was higher than that associated with the use of FNA needles (49%; P < 0.001); however, 19‐ or 22‐gauge FNB needles and 22‐ or 25‐gauge FNA needles were used in that study .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While it had been hoped that the EUS Trucut biopsy needle (TCB) would confer superior results compared to EUS-FNA, there was no significant improvement for diagnosis of SELs in a large prospective study 6. Recently, core biopsy using EUS-FNB has become available for sampling SELs, with diagnostic yields as high as 86 % being achieved with high rates of histologic sampling 8 9 10. However, a meta-analysis that examined the diagnostic yield and complication rates of EUS-FNA, TCB, and EUS-FNB for patients with gastrointestinal stromal tumors (GIST) demonstrated no significant differences between the techniques 10.…”
Section: Introductionmentioning
confidence: 99%